2017
DOI: 10.1186/s12864-017-3960-7
|View full text |Cite
|
Sign up to set email alerts
|

Development of a high-density linkage map and mapping of the three-pistil gene (Pis1) in wheat using GBS markers

Abstract: BackgroundThe wheat mutant line three-pistil (TP) exhibits three pistils per floret. As TP normally has two or three seeds in each of the florets on the same spike, there is the possibility of increasing the number of grains per spike. Therefore, TP is a highly valuable mutant for breeding and for the study of floral development in wheat. To map the three-pistil gene (Pis1), genotyping-by-sequencing single-nucleotide polymorphism (GBS-SNP) data from an F2 mapping population (CM28 × CM28TP) was used to construc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 27 publications
3
30
1
Order By: Relevance
“…It was systemically observed and studied from 2012, and our work showed that the multi-pistil trait can be stably transmitted to offspring. Our study showed that the multi-pistil trait is controlled by the single semi-dominant gene 12TP, differing from previous reports (Chen et al 1983;Peng 2003;Peng et al 2013;Yang et al 2017).…”
Section: Multi-pistil Gene 12tp Is a Semi-dominant Genecontrasting
confidence: 99%
See 2 more Smart Citations
“…It was systemically observed and studied from 2012, and our work showed that the multi-pistil trait can be stably transmitted to offspring. Our study showed that the multi-pistil trait is controlled by the single semi-dominant gene 12TP, differing from previous reports (Chen et al 1983;Peng 2003;Peng et al 2013;Yang et al 2017).…”
Section: Multi-pistil Gene 12tp Is a Semi-dominant Genecontrasting
confidence: 99%
“…Differences in cytoplasms (Wu et al 2000) or the presence of foreign cytoplasms (e.g., that of Aegilops kotschyi or Aegilops ventricosa), have been additionally shown to inhibit the expression of some 'tri-grain' genes (Ma et al 2000). The multi-pistil genes are located on 2DL, 5DS, 6BS and 6B (Tong and Tong 1984;Shen et al 1992;Ma et al 2000;Peng et al 2008;Wang et al 2009;Yang et al 2017). Map-based cloning, which requires finding closely linked markers, is the most effective method for the cloning of multipistil genes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of transcription factors (TF) binding motifs were analyzed with the PlantTFcat online tool (http://plantgrn.noble.org/PlantTFcat) [15]. SSRs (Simple Sequence Repeats), a type of molecular marker, is a potent tool for genetic studies and marker assisted selection (MAS) in many crops [16, 17]. In addition, in this research, we adopted the MISA search tool for SSR screening [18].…”
Section: Methodsmentioning
confidence: 99%
“…GBS is a cost-efficient and effective genotyping method (Yang et al, 2017;Bhattarai et al, 2018;Hackett et al, 2018). In this study, 390.30 Gb clean reads were generated.…”
Section: Genetic Purity Genetic Distance and Relationshipsmentioning
confidence: 99%